Implementasi Media Aplikasi Quizizz Terhadap Hasil Belajar pada Teks Negosiasi Siswa SMK Pemda Rantauprapat - Pohan, Muhammad Munawir; Nasution, Muhammad Bobbi Kurniawan; Kurniawan, Ridho (Altifani : Jurnal Pengabdian Masyarakat Ushuluddin, Adab, dan Dakwah, 2024)
This activity aims to analyze the effect of using the Quizizz application on student learning outcomes on negotiation text material. Quizizz is a game-based learning application that can be used to create interactive and interesting quizzes. This research was conducted in several stages, namely preparation, implementation, and evaluation. The results showed that the use of Quizizz significantly increased students' motivation and understanding of negotiation text material. Students became more active and motivated in learning, and showed an increase in participation and learning outcomes. The immediate feedback from Quizizz helped students understand and correct errors in real time. It was also found that Quizizz supports student-centered learning, by constructivist and behaviorism theories. However, constraints such as device availability and internet connection need to be considered to optimize the use of this application. It is recommended that schools ensure adequate technological support and provide training to teachers regarding the use of Quizizz. Gradual implementation and periodic evaluation are needed to ensure the effectiveness and adaptation of students to this learning method.